A method for estimating the cost to sequester carbon dioxide by delivering iron to the ocean. (1st January 2013) - Harrison, Daniel P.
The need to find economical methods of CO2 sequestration is now urgent. Ocean iron fertilisation has been suggested as a low cost mitigation option to capture and store carbon. However, previous methods of estimating the cost fail to account for many of the losses and offsets occurring over the storage period. A method for calculating the net carbon stored from iron fertilisation of high nutrient low chlorophyll ocean regions is provided. Ship based fertilisation of the Southern Ocean is considered as a case study, on average, a single fertilisation is found to result in a net sequestration of 0.01 t C km –2 for 100 years at a cost of US457 per tonne CO2 . Previous estimates of cost underestimate the economic challenge of distributing low concentrations of iron over large areas of the ocean surface, and the subsequent loss processes that result in only a small net storage of carbon per km 2 fertilised. Technologies that could lower the cost are discussed.